THE QUALITY OF HUMAN RESOURCE IN ENREKANG DISTRICT - Muh.Fihriz Khalik; Asbar Asbar; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2019)
The low level of Indonesian human resources is due to the lack of mastery of science and technology, because of the mental attitude and mastery of science and technology which can be the subjects or reliable development actors. In the framework of globalization, the preparation of education needs to be synergized with the demands of competition. Therefore the dimensions of competitiveness in HR are increasingly becoming an important factor so that efforts to boost the quality of human resources through education are demands that must be put forward. With mastery of science and technology, the community will be able to compete in the era of globalization. The ability to master science and technology in general must be owned by the community, especially residents of slum settlements on the banks of the east canal floods. Therefore, it takes care of academics to participate in helping improve the quality of human resources through a sewing course at the Enrekang district learning center. So that with the mastery of science and technology of mountain residents living in remote areas very far from science and technology facilities can change the standard of living to be better. Seeing such conditions, one of the steps that needs to be taken is to improve the quality of human resources. Improving the quality of human resources that starts early can affect the competitiveness of the individual. The step taken is to provide additional skills to those of productive age. One of the skills that will be given to the community is through a sewing course at the Enrekang district learning activity studio. With the skills through sewing courses in the Enrekang district learning activities studio, it is hoped that the community will be able to compete to get a better job.